Assessment of Elements Contributing Work Accidents in Construction Projects - Rahayu, Octavia; Widowati, Evi (Universitas Negeri Semarang, 2024)
Background: In 2019, the number of work accidents in the construction sector in Indonesia was still relatively high, with a total of 130,923 accidents. Education is one of the main factors influencing work accidents, with 16 people (61.5%) at risk of experiencing work accidents and 60 (60.6%) accidents due to non-compliance in using Personal Protective Equipment. In this research project, a work accident occurred, but the company still needs to record all of them entirely. This research aims to determine the relationship between education and the use of personal protective equipment with work accidents on the project. Methods: The design of this research is an observational analytic study with a cross-sectional design. The sample taken in the study was 123 workers, who were obtained using the Slovin formula and adding a minimum of 5% of the research sample size. Data analysis in this study used the chi-square test. Results: This study showed that there was a relationship between education and work accidents (p=0.004), and there was a relationship between the use of personal protective equipment such as safety helmets (p=0.000) and safety shoes (p=0.000) with work accidents on the project. Conclusion: Education and compliance in using safety helmets and safety shoes had a significant relationship with work accidents on the project.